2010 IEEE 18th International Workshop on Quality of Service (IWQoS) 2010
DOI: 10.1109/iwqos.2010.5542737
|View full text |Cite
|
Sign up to set email alerts
|

A switch-based approach to throughput collapse and starvation in data centers

Abstract: Abstract-Data center switches need to satisfy stringent lowdelay and high-capacity requirements. To do so, they rely on small switch buffers. However, in case of congestion, data center switches can incur throughput collapse for short TCP flows as well as temporary starvation for long TCP flows.In this paper, we introduce a lightweight hash-based algorithm called HCF (Hashed Credits Fair) to solve these problems at the switch level while being transparent to the end users. We show that it can be readily implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…And the performance may be incurred due to the congestion and retransmission mechanism provided by transmission control protocol (TCP). In order to overcome this problem, several schemes were proposed [4][5][6]. Among them, the HCF scheme proposed the credit based concept to balance the transmission rate of storage servers so that the congestion condition can be smoothed.…”
Section: Overview Of Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…And the performance may be incurred due to the congestion and retransmission mechanism provided by transmission control protocol (TCP). In order to overcome this problem, several schemes were proposed [4][5][6]. Among them, the HCF scheme proposed the credit based concept to balance the transmission rate of storage servers so that the congestion condition can be smoothed.…”
Section: Overview Of Related Workmentioning
confidence: 99%
“…From the service point of view, the cloud services can be divided into three models: the software as a service (SaaS), the platform as a service (PaaS), and the infrastructure as a service (IaaS). Although the cloud computing provides flexible resource allocation, recently, it was found that, due to the characteristics of TCP protocol, the existence of in-cast issue in the storage area network greatly affects the processing performance of the cloud computing [1][2][3][4]. Thus, to adopt more servers for parallel downloading does not mean higher received throughput.…”
Section: Introductionmentioning
confidence: 99%